Losing its lustre - a narrative of the gold mining communities of the western Witwatersrand focusing on the impact of post 1994 legislation and its ability to transform these communities into flourishing towns or reduce them to ghost towns in the context of a declining gold mining industry - Breitenbach, Danette (My University, 2018)
South Africa became a democracy in 1994. The new government faced the task of transforming the country from one where the majority of the population had been discriminated against to one where everyone shares in the benefits of the country. One of the biggest culprits of discrimination pre-1994 was the mining industry. No more was this more evident than in mining communities. To change this, legislation was passed, specifically is the Mining Petroleum Resources Development Act (MPRDA) of 2002. At its heart it transferred ownership of mining rights to the State (previously mining companies owned mining rights). To be awarded a mining right, the mining company needs to satisfy a number of criteria, one of which is the submission of Social and Labour Plan (SLP) which addresses the socio-economic development projects the company will undertake and by when for mine workers and the host mining community not only during the life of the mine but also following mine closure. This “system” has been in working for 16 years. This research examines how that legislation has impacted mining communities, specifically in the West Wits region where gold mining towns were established as early as the discovery of gold. These towns experienced the heydays of gold up to the late 1980s. Today, however, the mines are a far cry from these glory days. It is in this context that the SLP as mechanism to mitigate years of a system that discriminated against most South Africans, including mining communities, is examined. The findings are a mixed bag of an amalgam of success and failure, and of satisfaction and dissatisfaction. This report consists of two sections; the first is a narrative writing style presenting research in a long-form narrative. The second is the method document which sets out the academic research supporting this work, how the research was conducted and why.
A research report submitted in partial fulfilment to the degree of Master of Arts, Faculty of Humanities, School of Journalism and Media, University of the Witwatersrand, Johannesburg, 2018
Keywords: Strategic planning; Municipal services; Local government--South Africa